Governance of writing: the scission between modernity and hypermodernity “cite and parentheses” (2017)
Nowadays Academic writing reflects the scission between modernity and hypermodernity. In the early modernity writing had as aim to show the constant thinking battle the writers dealt with. Sciences preeminence, scientific society’s role, the birth of a researcher individual and the emergence of scientific journals encourage the use of footnotes. Parentheses are imposed by technology power and a society of control. The present paper holds that today’s writing shows simple thoughts, absence of intensity and plasticity of the appearance. Contemporary practices of academic writing show the writing governance whose practices give the importance to topics about thinking issues.